FORMATION OF THE MAIN COMPONENTS OF THE COMPLEX SYSTEM OF AGRARIAN MARKETING FOR ENTERPRISES IN THE AGRICULTURAL BUSINESS SPHERE - Bagorka, Maria (Socio-economic relations in the digital society, 2023)
The purpose of our research is to generalize theoretical and methodological approaches to the formation of a complex agricultural marketing system, to develop recommendations for the implementation of the main elements of this system in the practical activities of enterprises in modern conditions and to allocate marketing reserves aimed at increasing the competitiveness of trading enterprises in modern business conditions. It is proved that the formation and functioning of the enterprise agricultural marketing system should be carried out on the basis of a systematic approach and synergistic combination of marketing tools, taking into account the characteristics of products, market, behaviour and consumer needs, with the marketing management system, on which the successful activity of the enterprise in the market environment depends. The main components of the integrated agricultural marketing system are defined and proposals for the implementation of this system in the activities of trading enterprises are provided. The importance of the implementation of a complex agrarian marketing system lies in the combination of elements of the Marketing-mix complex and the marketing management system, with the aim of prompt response to changes in the market environment. We are sure that the expected results can be achieved only in the interaction of these components of the marketing system, the use of individual elements, in our opinion, will not give a full-fledged result.